Mental health stigma and health-seeking behaviors amongst pregnant women in Vietnam: a mixed-method realist study - Le Minh Thi; Ana Manzano; Bui Thi Thu Ha; Le Thi Vui; Nguyen Thai Quynh-Chi; Doan Thi Thuy Duong; Kimberly Lakin; Sumit Kane; Tolib Mirzoev; Do Thi Hanh Trang (BMC, 2024)
Abstract Background Approximately 15% of women in low-and middle-income countries experience common perinatal mental disorders. Yet, many women, even if diagnosed with mental health conditions, are untreated due to poor quality care, limited accessibility, limited knowledge, and stigma. This paper describes how mental health-related stigma influences pregnant women's decisions not to disclose their conditions and to seek treatment in Vietnam, all of which exacerbate inequitable access to maternal mental healthcare. Methods A mixed-method realist study was conducted, comprising 22 in-depth interviews, four focus group discussions (total participants n = 44), and a self-administered questionnaire completed by 639 pregnant women. A parallel convergent model for mixed methods analysis was employed. Data were analyzed using the realist logic of analysis, an iterative process aimed at refining identified theories. Survey data underwent analysis using SPSS 22 and descriptive analysis. Qualitative data were analyzed using configurations of context, mechanisms, and outcomes to elucidate causal links and provide explanations for complexity. Results Nearly half of pregnant women (43.5%) would try to hide their mental health issues and 38.3% avoid having help from a mental health professional, highlighting the substantial extent of stigma affecting health-seeking and accessing care. Four key areas highlight the role of stigma in maternal mental health: fear and stigmatizing language contribute to the concealment of mental illness, rendering it unnoticed; unconsciousness, normalization, and low literacy of maternal mental health; shame, household structure and gender roles during pregnancy; and the interplay of regulations, referral pathways, and access to mental health support services further compounds the challenges. Conclusion Addressing mental health-related stigma could influence the decision of disclosure and health-seeking behaviors, which could in turn improve responsiveness of the local health system to the needs of pregnant women with mental health needs, by offering prompt attention, a wide range of choices, and improved communication. Potential interventions to decrease stigma and improve access to mental healthcare for pregnant women in Vietnam should target structural and organizational levels and may include improvements in screening and referrals for perinatal mental care screening, thus preventing complications.